The Relationship Between Physical Activity And Cognitive Function In The Elderly In Rw 12 Kp. Haur Cucuk Sumbersari Village - Sri Kusdiyanty, Inggit; Iqbal Martani, Muhammad; Suprihatin, Neneng; Nur Octavia, Anggaeni (HealthCare Nursing Journal, 2025)
As the elderly population increases, the problem of diseases due to degenerative processes is increasing, the aging process is often accompanied by a decrease in cognitive abilities. In Indonesia, the number of elderly individuals experiencing cognitive function impairments has risen to 121 million. Engaging in physical activity is considered one of the key strategies to mitigate the risk of cognitive decline. This research seeks to explore the correlation between physical activity and cognitive function among the elderly population. This study utilizes a quantitative approach with an analytical survey design, employing a cross-sectional methodology. It was carried out in August 2024, with the research subjects of 51 elderly people in the RW 12 Kp. Haur Cucuk, Sumbersari Village using purposive sampling techniques. Data were collected by providing a PASE modification questionnaire for physical activity and an MMSE questionnaire for cognitive function. The data were analyzed through frequency distribution and the Chi-Square test. The study revealed that 56.9% of the elderly exhibited high levels of physical activity, while 51% demonstrated strong cognitive function. The Chi-square test yielded a p-value of 0.000, which is less than the 0.05 threshold. A significant correlation was found between physical activity and cognitive function among the elderly in the RW 12 Kp. Haur Cucuk Sumbersari Village. Health workers at the health center can facilitate physical activity activities for the elderly such as leisurely walks, gymnastics for the elderly and others. This activity is carried out regularly to support the physical and cognitive health of the elderly.